The Scientific Contribution of the Al-Kindy College Medical Journal to the World Literature on the COVID-19 Pandemic - Al-Mendalawi, Mahmood D. (AL-Kindy College Medical Journal, 2023)
The beginning of COVID-19 in Wuhan, China in late December 2019 and its worldwide transmission has led the World Health Organization to formally address the pandemic. The pandemic has imposed influential impacts on different environmental, economic, social, health, and living aspects. Publishing in scholastic journals was not immune from these impacts.